PENGUJIAN HIPOTESIS KUZNETS - Sri Isnowati (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
Area development is generally focused on economics development through effort in economic growth. But sometime, it becomes a dilemma between emphasizing economic growth and reducing income imbalance. High growth has no guarantee that income imbalance will be low. This research will test Kuznets hypothesis about the relation between economic growth and income imbalance in Development Area I in Central Java. Williamson index and Entrophy Theil index are used to measure income imbalance. The research result shown that income imbalance in Development Area I in Central Java is increasing. Kuznets hypothesis is effective in Development Area I in Central Java. Key word: Economic Growth, income Imbalance, Williamson Index, Entrophy TheilIindex, and Kuznets Hypothesis.